The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/jm0506423
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent and Selective Inhibitors of PDGF Receptor Autophosphorylation

Abstract: We report the structure-activity relationship of quinoline and quinazoline derivatives, which include urea, thiourea, urethane, and acylthiourea groups, as inhibitors of the platelet-derived growth factor (PDGF) receptor autophosphorylation. Our previous studies showed that the quinoline and quinazoline derivatives including urea, thiourea, and carbamate groups were highly potent compounds as the PDGF receptor autophosphorylation inhibitor, but these compounds did not exhibit receptor selectivity between the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
(19 reference statements)
1
39
0
Order By: Relevance
“…4A). We then blocked either PDGFR activity using PDGFR tyrosine kinase inhibitor V, which inhibits ligand-induced PDGFR phosphorylation and kinase activity (45), or endogenous PDGFR ligands using PDGF-B and pan-PDGF neutralizing Abs. Results showed that invadosome formation induced by PDGF-B in control synovial cells or already elevated in RA cells was abolished by the addition of PDGF neutralizing Abs or PDGFR tyrosine kinase inhibitor V (Fig.…”
Section: Signaling Through Pdgfr Is Required For the Enhanced Invadosmentioning
confidence: 99%
“…4A). We then blocked either PDGFR activity using PDGFR tyrosine kinase inhibitor V, which inhibits ligand-induced PDGFR phosphorylation and kinase activity (45), or endogenous PDGFR ligands using PDGF-B and pan-PDGF neutralizing Abs. Results showed that invadosome formation induced by PDGF-B in control synovial cells or already elevated in RA cells was abolished by the addition of PDGF neutralizing Abs or PDGFR tyrosine kinase inhibitor V (Fig.…”
Section: Signaling Through Pdgfr Is Required For the Enhanced Invadosmentioning
confidence: 99%
“…By analyzing the relationship between molecular structure and activity, it was found that the compound, in which both R 1 and R 2 are OCH 3 or CH 3 , or one is OCH 3 and the other is CH 3 , possesses relatively high phytotoxic activity.…”
Section: Phytotoxic Activitymentioning
confidence: 99%
“…Heterocyclic acylthioureas exhibit excellent biological activities, such as fungicidal, 1) insecticidal, 2) antitumor 3) and regulation of plant growth, 4) and some acylthioureas containing 4,6-disubstitued pyrimidinyl possess herbicidal activity. 5) Additionally, N-4,6-disubstitued pyrimidinyl acylthiourea can be transformed into fused heterocyclic derivative (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of quinazolinone 5 in refluxing phosphorus oxychloride afforded the chloroquinazoline derivative in good yield (>90%). In series B, compound 10 was prepared according to procedures previously described by Furuta et al 41 using methyl 2-amino-4,5-dimethoxybenzoate 8 as starting material. To prepare series C, the same synthesis route was employed as for series A.…”
Section: Chemistrymentioning
confidence: 99%